Cover Picture: Rhodium‐Complex‐Linked Hybrid Biocatalyst: Stereo‐Controlled Phenylacetylene Polymerization within an Engineered Protein Cavity (ChemCatChem 5/2014). Issue 5 (May 2014) - Fukumoto, Kazuki; Onoda, Akira; Mizohata, Eiichi; Bocola, Marco; Inoue, Tsuyoshi; Schwaneberg, Ulrich; Hayashi, Takashi
<x xml:space="preserve">Abstract</x> Fancy a game of mutajenga? The cover picture represents the reengineering of a hybrid biocatalyst containg a rhodium complex within a β‐barrel scaffold by computationally guided design and mutagesis as playing with building blocks to shape the circular wall. In their Full Paper on p. 1229 ff., K. Fukumoto et al. report how the hybrid biocatalyst with a covalently linked rhodium complex inside the cavity of nitrobindin promotes the polymerization of phenylacetylene. The appropriate structural optimization of the cavity by mutagenesis is found to provide polyphenylacetylene with a trans content of 82 % at 25 °C, pH 8.0. The X‐ray crystal structure of the hybrid biocatalyst reveals that the rhodium complex is located in the ‐barrel cavity without any perturbation of the whole protein structure. The crystal structure and molecular modelling support the fact that the stereoselectivity is enhanced by effective control of monomer access to the rhodium complex within the limited space of the protein cavity.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>